Análise técnico econômica de substituição de lâmpadas de descarga de alta pressão por conjuntos LEDS em subestação aberta - Mahuad, Gustavo Ribeirete (2023)
This work studies the case of replacing high-pressure discharge lamps with LED sets in the Ponta Grossa Norte open substation yard, located in Paraná, Brazil, and managed by COPEL, in order to verify with the data obtained that the LED lighting system has economic return on investment greater than the system using sodium vapor lamps over the years. The development of the chosen theme is motivated by the current situation of the substation, mentioned above, which will be signaled, as it uses sodium vapor lamps by substation standard. When presenting the study, results were obtained that prove the economic viability of the LED system, analyzing factors such as equipment change, equipment life, electricity consumption, labor, maintenance, infrastructure and cabling.